Risk of disability and mortality due to overweight in a Finnish population. Issue 6756 (13th October 1990) - Rissanen, A; Heliövaara, M; Knekt, P; Reunanen, A; Aromaa, A; Maatela, J
Abstract : OBJECTIVE--To investigate the effect of overweight on premature mortality and work disability in young and middle aged Finns. DESIGN--Prospective cohort study based on data collected in the multiphasic health examinations by the Social Insurance Institution of Finland from 1966 to 1972 and follow up until 1982. SETTING--34 Communities throughout Finland. SUBJECTS--12, 053 Women and 19, 076 men who were employed and aged 25-64 at baseline. MAIN OUTCOME MEASURES--Mortality and work disability pensions from all and specified causes. RESULTS--Body mass index was a weak predictor of death but a strong predictor of early work disability, which increased linearly with body mass index. After adjustment for age, geographical region, occupation, and smoking the relative risks of work disability for women and men with a body mass index greater than or equal to 30 kg/m2 were, respectively, 2.0 (95% confidence interval 1.8 to 2.3) and 1.5 (1.3 to 1.7) when compared with those of subjects with body mass index less than 22.5 kg/m2. The increased risks were due to an excess of cardiovascular and musculoskeletal diseases but not of mental diseases. One fourth of all disability pensions from cardiovascular and musculoskeletal causes in women and half as many in men could be attributed to overweight (body mass index greater than 25 kg/m2) alone. CONCLUSIONS--Though modest overweight has little impact on mortality it predicts severe functional impairment. A considerable proportion of work disability pensions could probably be prevented by efficient weight control.